Controlled and Reversible Stepwise Growth of Linear Copper(I) Chains Enabled by Dynamic Ligand Scaffolds. Issue 51 (23rd November 2017) - Rivada‐Wheelaghan, Orestes; Aristizábal, Sandra L.; López‐Serrano, Joaquín; Fayzullin, Robert R.; Khusnutdinova, Julia R.
Abstract: Reversible stepwise chain growth in linear Cu I assemblies can be achieved by using the dynamic, unsymmetric naphthyridinone‐based ligand scaffoldsL1 andL2 . With the same ligand scaffolds, the length of the linear copper chain can be varied from two to three and four copper atoms, and the nuclearity of the complex is easily controlled by the stepwise addition of a Cu I precursor to gradually increase the chain length, or by the reductive removal of Cu atoms to decrease the chain length. This represents a rare example of a stepwise controlled chain growth in extended metal atom chains (EMACs). All complexes are formed with excellent selectivity, and the mutual transformations of the complexes of different nuclearity were found to be fast and reversible. These unusual rearrangements of metal chains of different nuclearities were achieved by a stepwise "sliding" movement of the naphthyridinone bridging fragment along the metal chain. Abstract : Copper chain traffic control : The stepwise growth of copper(I) linear chain complexes was achieved with dynamic ligand scaffolds. Complexes containing the same ligand and one, two, three, or four Cu I atoms interconvert reversibly in a process that is controlled by the stoichiometry, solvent polarity, and redox transformations.